PROSEDUR REGISTRASI OBAT TRADISIONAL OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DI KOTA PEKANBARU - Fransiscus Rio Ganda; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Traditional drug registration is the registration procedure and evaluation of the drug to obtain marketing authorization. Circulation is any activity or series of activities distribution or delivery of drugs, both in the context of trade, not trade, or alienation. The purpose of drug registration is to protect the public from the drug that did not meet the requirements of efficacy, safety, quality and public health.BBPOM Pekanbaru found some illegal drug products sold in the market and are not registered that contain hazardous materials. After checking it turns out a lot of medicinal products sold without a marketing authorization and already violates the rules because it could not demonstrate that the requirements of the drug product is manufactured properly and meets applicable standards. Illegal traditional medicinal products do not have a marketing authorization and many do not have a business license the industry, in terms of the price of traditional medicine was the existence of illegal troubling because it will cause unhealthy competencies with legal herbs assured quality From the description above, the writer interested to examine this issue under the title " Traditional Medicines Registration Procedure by the Center for Food and Drug Administration (BBPOM) In the city of Pekanbaru".Keywords: Procedures, Registration, Traditional Medicine